2018
DOI: 10.1038/s41477-018-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

Generation of self-compatible diploid potato by knockout of S-RNase

Abstract: Re-domestication of potato into an inbred line-based diploid crop propagated by seed represents a promising alternative to traditional clonal propagation of tetraploid potato, but self-incompatibility has hindered the development of inbred lines. To address this problem, we created self-compatible diploid potatoes by knocking out the self-incompatibility gene S-RNase using the CRISPR-Cas9 system. This strategy opens new avenues for diploid potato breeding and will also be useful for studying other self-incompa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(129 citation statements)
references
References 22 publications
0
117
0
Order By: Relevance
“…Both studies were highly successful in terms of the specific traits that they targeted, doubling the yield of S pimpinellifolium and increasing lycopene contents to 500% of control levels (Li et al, 2018b;Zs€ og€ on et al, 2018). A further example of the power of gene editing in breeding is provided by the recent demonstration that knocking out the self-incompatibility gene S-RNase allows redomestication of potato into an inbred-line based diploid crop, representing a promising alternative to traditional clonal propagation of tetraploid potato (Ye et al, 2018). The study demonstrated the utility of this approach in four different Solanum tuberosum clones, thus opening up the myriad possibilities in future diploid breeding, which will likely greatly facilitate both basic research and genetic improvement of potato and self-incompatible crops.…”
Section: De Novo Domesticationmentioning
confidence: 99%
“…Both studies were highly successful in terms of the specific traits that they targeted, doubling the yield of S pimpinellifolium and increasing lycopene contents to 500% of control levels (Li et al, 2018b;Zs€ og€ on et al, 2018). A further example of the power of gene editing in breeding is provided by the recent demonstration that knocking out the self-incompatibility gene S-RNase allows redomestication of potato into an inbred-line based diploid crop, representing a promising alternative to traditional clonal propagation of tetraploid potato (Ye et al, 2018). The study demonstrated the utility of this approach in four different Solanum tuberosum clones, thus opening up the myriad possibilities in future diploid breeding, which will likely greatly facilitate both basic research and genetic improvement of potato and self-incompatible crops.…”
Section: De Novo Domesticationmentioning
confidence: 99%
“…SC was retained in these trees over several years without obvious adverse effects. Much more recently, CRISPR-induced knockouts of S-RNase have been used to generate SC diploid lines for breeding purposes in potato (Solanum tuberosum L.) (Ye et al, 2018;Enciso-Rodriguez et al, 2019) (Figure 1B).…”
Section: Different Sources Of Sc: a Favorable Trait For Yield Enhancementioning
confidence: 99%
“…However, the introgression of the S. chacoense Sli gene into other potatoes is time-consuming and may carry along undesirable traits such as long stolons or high tuber glycoalkaloid content. CRISPR knock-out of the S-RNase gene has recently been shown to be another viable method to generate SC potato lines avoiding linkage drag of undesirable traits associated with Sli (Ye et al, 2018;Enciso-Rodriguez et al, 2019). This important milestone has implications for the replacement of the current tetraploid asexually propagated potato with a diploid inbred line-based crop propagated by seeds (Jansky et al, 2016).…”
Section: Ways Of Achieving Sc and Its Role In Hybrid Breedingmentioning
confidence: 99%
“…In summary, already at this early stage (Fernie and Yan, ), gene editing can be used to: activate or suspend the function of a gene (Qi et al ., ); create multiple different alleles of a gene (Rodriguez‐Leal et al ., ); edit any base (Gaudelli et al ., ); repair deletions (Dahan‐Meir et al ., ); add genes that do not exist in the original genome (Park et al ., ); and delete any sequence, including large chromosomal fragments or even entire chromosomes (Xiao et al ., ). CRISPR has successfully been used in many important crop species including, but not limited to, the cereals Hordeum vulgare (barley; Lawrenson et al ., ), Oryza sativa (rice; Shan et al ., ; Li et al , ), Triticum aestivum (wheat; Shan et al , ; Zhang et al ., ) and Zea mays (maize; Shi et al ., ), as well as Brassica oleracea (Lawrenson et al , ), Citrus (Peng et al ., ), Cucumis sativus (cucumber; Chandrasekaran et al ., ), Glycine max (soybean; Demorest et al ., ), Solanum lycopersicum (tomato; Cermak et al ., ), and Solanum tuberosum (potato; Clasen et al ., ; Ye et al ., ), with applications in novel species published on a monthly, if not weekly, basis. In terms of agricultural application, it is essential to realise that that the Cas9 enzyme is, in effect, a biological mutagen, a fact that needs to be conveyed more clearly to politicians as well as to the general public.…”
Section: The Advent and Adoption Of Genome Editing In Plantsmentioning
confidence: 99%